Classification of Pelvic Ring Fractures in Skeletonized Human Remains. (7th November 2014) - Báez‐Molgado, Socorro; Bartelink, Eric J.; Jellema, Lyman M.; Spurlock, Linda; Sholts, Sabrina B.
Abstract: Pelvic ring fractures are associated with high rates of mortality and thus can provide key information about circumstances surrounding death. These injuries can be particularly informative in skeletonized remains, yet difficult to diagnose and interpret. This study adapted a clinical system of classifying pelvic ring fractures according to their resultant degree of pelvic stability for application to gross human skeletal remains. The modified Tile criteria were applied to the skeletal remains of 22 individuals from the Cleveland Museum of Natural History and Universidad Nacional Autónoma de México that displayed evidence of pelvic injury. Because these categories are tied directly to clinical assessments concerning the severity and treatment of injuries, this approach can aid in the identification of manner and cause of death, as well as interpretations of possible mechanisms of injury, such as those typical in car‐to‐pedestrian and motor vehicle accidents.